Exploring dabai (Canarium odontophyllum), indigenous fruit of Borneo: a review of nutritional values, potential uses, emerging application in essential oil processing and health benefits - Hamzah, Muhammad Hazwan; Mohd Basri, Mohd Salahuddin; Maringgal, Bernard; Mohd Ali, Maimunah; Wondi, Mohd Hafizz; Che Man, Hasfalina; Abdulloh, Sukardi Gatuk (Multidisciplinary Digital Publishing Institute, 2022)
Dabai (Canarium odontophyllum) is a fruit-bearing plant native to Borneo. Its fruit is an indigenous seasonal fruit that is considered to be underutilized due to its short shelf life. However, new products have been developed to ensure a continuous supply of dabai fruit throughout the year. Hence, the exploration of dabai fruits in characterizations and utilization for food products and essential oil has expanded exponentially. This review addresses the nutritional values, health benefits, potential food products, and essential oil processing of dabai fruit. All parts of dabai fruit, such as the pulp, skin, and kernel, contain a considerable amount of bioactive compounds, dietary fiber, and nutrients. Moreover, dabai fruit has also been proven to have health benefits such as an antioxidant capacity, cholesterol reduction, diabetes type 2 prevention, and reduction in the risk of heart disease. Some potential dabai-based food products and oil processing of dabai are also highlighted. The future perspectives and challenges concerning the potential uses of dabai are critically addressed at the end of this review. Based on this review, it is proven that dabai has various health benefits and represents a potential breakthrough in the agricultural and food industries.